Vitamin D and Cancer - Vuolo, Laura; di somma, carolina; Faggiano, Antongiulio; Colao, Annamaria A. (Frontiers in Endocrinology, 2012)
Vitamin D system is a complex pathway that includes precursors, active metabolites, enzymes and receptors activating several molecular pathways and mediating a multitude of functions. In addition to the classical role of vitamin D metabolites in calcium and bone homeostasis, many in vitro and in vivo studies recognized several "non calcemic" effects involved in host defence, inflammation, immunity and cancer processes. The aim of this review is to highlight the relationship between vitamin D and cancer, summarizing several mechanisms proposed to explain the potential protective effect of vitamin D against the development and progression of cancer. Vitamin D acts like a transcription factor that influences central mechanisms of tumorigenesis: growth, cell differentiation and apoptosis. In addition to cellular and molecular studies, epidemiological surveys have shown that sunlight exposure and consequent increased circulating levels of vitamin D are associated not only with reduced occurrence but also with reduced mortality for different histological types of cancer. Another recent field of interest concerns polymorphisms of vitamin D receptor: in this context, preliminary data suggest that vitamin D receptor polymorphisms more frequently associated with tumorigenesis are Fok1, Bsm1, Taq1, Apa1, EcoRV, Cdx2, although further studies are needed to clarify any discrepancies. In this review, the relationship between vitamin D and cancer is discussed.